Single event multilevel surgery in spastic patient : A Hospital Tengku Ampuan Afzan (HTAA) experience - Nik Abdul Adel, Nik Alyani; Awang, Mohd Shukrimi; A. Y, Yusma; Abdul Razak, Ardilla Hanim; Loh, Li Long (Malaysian Orthopaedic Association (MOA), 2019)
INTRODUCTION: Single event multilevel surgery (SEMLS) is common procedure to improve gait and functioning of children with spastic cerebral palsy (CP).The case series is aim to observe the post-operative outcomes of gross motor function (GMFCS) and hip migration index (MI) in spastic patient.